2022
DOI: 10.1002/adsc.202200750
|View full text |Cite
|
Sign up to set email alerts
|

Visible Light‐Induced Radical‐Radical Coupling: One‐Pot Synthesis of 6‐Benzyl‐6‐hydroxyindolo[2,1‐b]quinazolin‐12(6H)‐ones from Isatins and Potassium Benzyl Trifluoroborates

Abstract: A method for one-pot synthesis of 6-benzyl-6-hydroxyindolo[2,1-b]quinazolin-12(6H)-ones from isatins and potassium benzyl trifluoroborates was developed. Bioactive tryptanthrin skeleton can be constructed by visible light-induced radical-radical cross coupling, in which CÀ C and CÀ N bonds are formed in one pot. With this method, 31 products were synthesized directly from isatins in 22-86% yields. Notable features of this method include mild reaction conditions, metal-and external oxidant-free, and direct cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…3.1.1.5 One-pot synthesis of 6-benzyl-6-hydroxyindolo[2,1-b] quinazolin-12(6H)-ones. In 2022, He's group 33 investigated the reaction between isatin 1 and potassium benzyl trifluroborate 50 with 1,2,3,5-tetrakis(carbazol-9-yl)4,6-dicyanobenzene (4CzIPN) as photocatalyst under irradiation by 9 W blue LEDs and obtained the product in low yields (Scheme 30). Based on control experiments, they showed that the reaction required both light and a catalyst.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
“…3.1.1.5 One-pot synthesis of 6-benzyl-6-hydroxyindolo[2,1-b] quinazolin-12(6H)-ones. In 2022, He's group 33 investigated the reaction between isatin 1 and potassium benzyl trifluroborate 50 with 1,2,3,5-tetrakis(carbazol-9-yl)4,6-dicyanobenzene (4CzIPN) as photocatalyst under irradiation by 9 W blue LEDs and obtained the product in low yields (Scheme 30). Based on control experiments, they showed that the reaction required both light and a catalyst.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
“…In 2022, Guan and colleagues elucidated two routes (Method A and Method B) for the synthesis of tryptanthrin derivatives (Scheme 13). [39] Method A: Using two molecules of isatins 1 and potassium benzyl trifluoroborates 27 as the starting materials, the 6‐benzyl‐6‐hydroxyindolo[2,1‐b]quinazolin‐12(6H)‐ones 28 were obtained by visible light‐induced radical‐radical coupling. However, this strategy is limited by the structural diversity of the products.…”
Section: Ring‐expansion Of Isatinmentioning
confidence: 99%
“…The skeletal structure of tryptanthrin 73 includes the backbone of both indoles and quinoxalinones. A wide variety of drug molecules can be designed from tryptanthrins; hence, various pathways are used to synthesise them, and one such standard method is from isatin [53] . The building block of various naturally occurring alkaloids is constituted by ring‐fused quinazolinones such as rutaecarpine 74 , loutonin A 75 , mackinazolinone 76 , febrifugine 77 , vasicinone 78 , etc.…”
Section: Quinazolinones and Quinazoline‐24‐dionesmentioning
confidence: 99%
“…Here, they conducted experiments with different metal catalysts and finally concluded that FeCl 3 was the most appropriate one for the ring‐opening reaction of isatin with trifluroacetimidoyl chlorides 99 to produce 2‐(trifluoromethyl)quinazolin‐4(3 H )‐ones 103 (Scheme 21). Also, Huang and his group [53] focused on constructing 6‐benzyl‐6‐hydroxyindolo[2,1‐ b ]quinazolin‐12(6 H )‐ones 105 from a pseudo‐two‐component reaction of isatin and potassium benzyl trifluoro borates 104 in an inexpensive way. Here, two moles of isatin 1 reacted with one mole of potassium benzyl trifluoroborate 104 in the presence of a light source and a photocatalyst, 1,2,3,5‐tetrakis(carbazole‐9‐y l )4,6‐dicyanobenzene in a suitable solvent as shown in Scheme 22.…”
Section: Quinazolinones and Quinazoline‐24‐dionesmentioning
confidence: 99%